2012
DOI: 10.1007/s10620-012-2266-5
|View full text |Cite
|
Sign up to set email alerts
|

Colonoscopy Preparation: Polyethylene Glycol with Gatorade Is as Safe and Efficacious as Four Liters of Polyethylene Glycol with Balanced Electrolytes

Abstract: Background Four liters of polyethylene glycol 3350 with balanced electrolytes for colonoscopy preparation has had poor acceptance. Another approach is the use of electrolyte-free PEG combined with 1.9L of Gatorade. Despite its widespread use, there are no data on metabolic safety and minimal data on efficacy. Our aim was to assess the efficacy and electrolyte safety of these two PEG-based preparations. Methods This was a prospective, randomized, single-blind, non-inferiority trial. Patients were randomized t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…In the remaining 4 studies, including 1 study that used 306 g rather than 238 g, the proportion of patients having an adequate bowel preparation was comparable with PEG-3350 powder and 4 L PEG-ELS (29)(30)(31). Tolerability based on taste and overall experience was better with PEG-3350 powder than with 4 L PEG-ELS in 4 studies ( 73,80,84,161 ), and no diff erence in tolerability was observed in 1 series ( 69 ).…”
Section: Sodium Picosulfatementioning
confidence: 89%
See 1 more Smart Citation
“…In the remaining 4 studies, including 1 study that used 306 g rather than 238 g, the proportion of patients having an adequate bowel preparation was comparable with PEG-3350 powder and 4 L PEG-ELS (29)(30)(31). Tolerability based on taste and overall experience was better with PEG-3350 powder than with 4 L PEG-ELS in 4 studies ( 73,80,84,161 ), and no diff erence in tolerability was observed in 1 series ( 69 ).…”
Section: Sodium Picosulfatementioning
confidence: 89%
“…Although hyponatremia is a potential risk when using a hypotonic lavage solution such as PEG powder, no statistical diff erences in serum electrolyte levels were observed in 3 studies that compared PEG powder vs. 4 L PEG-ELS ( 80,84,161 ). Reports of hyponatremia have occurred when administered the evening before, but not with split-dose regimens ( 162 ) .…”
Section: Sodium Picosulfatementioning
confidence: 99%
“…Previous studies compared a PEG-3350+SD regimen vs. 4-L PEG-ELS (GoLytely), demonstrating increased patient satisfaction and tolerability in the PEG-3350 group while producing similar rates of high-quality bowel preparation (15)(16)(17). We chose to compare PEG-3350+SD+B to the FDA-approved PM/AM split-dose PEG-AA.…”
Section: Discussionmentioning
confidence: 99%
“…One study using PEG-3350 in a community setting resulted in good-quality bowel preparations and patient tolerability (14). Subsequent studies compared PEG-3350+SD with 4-L PEG-ELS, some concluding PEG-3350 as a non-inferior bowel preparation (15)(16)(17), while others showed higher quality preparations with 4-L PEG-ELS (10,18). There have been no head-tohead comparative trials of PEG-3350+SD+B vs. PEG-AA.…”
Section: Introductionmentioning
confidence: 99%
“…However, this difference was not seen for theSD regimen of PEGAand the clinical relevance of a slightly lower score is lessened given that the endoscopist can deal with residual stool at the time of the procedure. Prior studies also have compared 4-L PEG solutions (PEG-ELS) with 2-L PEG solutions and bisacodyl tablets (PEG) and found no significant differences in bowel preparation effectiveness using the BBPS scale [20,21] . However, one randomized trial, and a recent metaanalysis of PEG bowel preparations, demonstrated statistically significantly fewer satisfactory bowel preparation scores as compared to PEG-ELS solutions using either the BBPS or Ottawa Preparation Scale (OPS) [22,23] .…”
Section: Discussionmentioning
confidence: 99%